Application of Three-Dimensional Media of The Shape of The Earth's Surface for The Learning of Visually Impaired - Prasetya, Sukma Perdana; Imron, Ali; Riyadi, Riyadi; Chanthoeurn, Dock (International Journal of Social Learning (IJSL), 2023)
Blind students cannot use their senses properly; they can learn by relying on their senses of touch and hearing. For this reason, it is necessary to have teaching media that depend on the importance of communication or hearing to recognize material on the shape of the Earth's surface. This research aims to increase the learning interest of blind students in the fabric of the Earth's surface in social science subjects. This research method is pre-experimental, with blind students being treated with 3D media and observing their responses. The application of 3D media in the form of the Earth's surface in learning for blind children involved eight students. It was implemented in three junior high schools in East Java, Indonesia. These schools include Special Schools in Bojonegoro, Surabaya, and Sidoarjo. The results of the application of 3D media show that using 3D learning media in the form of the Earth's surface in the teaching and learning process can generate new desires and interests, generate motivation, and stimulate learning activities, even bringing psychological influences on blind students. 3D learning media can also help improve students' understanding, present data excitingly and reliably, facilitate data retention, and obtain information about the shape of the Earth's surface.